The Linguistic Philosophy of Noam Chomsky - Barman, Binoy (Philosophy and Progress, 2014)
Noam Chomsky, one of the most famous linguists of the twentieth century, based his linguistic works on certain philosophical doctrines. His main contribution to linguistics is Transformational Generative Grammar, which is founded on mentalist philosophy. He opposes the behaviourist psychology in favour of innatism for explaining the acquisition of language. He claims that it becomes possible for human child to learn a language for the linguistic faculty with which the child is born, and that the use of language for an adult is mostly a mental exercise. His ideas brought about a revolution in linguistics, dubbed as Chomskyan Revolution. According to him, the part of language which is innate to human being would be called Universal Grammar. His philosophy holds a strong propensity to rationalism in search of a cognitive foundation. His theory is a continuation of analytic philosophy, which puts language in the centre of philosophical investigation. He would also be identified as an essentialist. This paper considers various aspects of Chomskys linguistic philosophy with necessary elaborations. DOI: http://dx.doi.org/10.3329/pp.v51i1-2.17681